Determination of The Physical and Mechanical Properties of the Materials Used in The Northern City Walls of Historical Sinop Castle - Kiliç Demi̇rcan, Rüya; Ünay, Ali̇ İhsan; Kaplan, Gökhan (IOP Publishing, 2019)
Turkey is a country that has hosted many civilizations due to its geographical location. The artefacts of these civilizations constitute important historical heritages of the country. The preservation, restoration and strengthening of historical artefacts and their transfer to future generations are the responsibilities of every country. Historical Sinop Castle that investigated in this study locates in the Sinop city where takes place northernmost of Turkey. Sinop province is a half island due to its geographical position and it is known that the castle walls were built due to the protection of this city. It is not known exactly when the historic Sinop Castle was built. It is estimated the time period of built could be 8th century B.0 based on excavations. It is known that to hosted the Milets, the Cimmerians, the Persians, the Romans, the Byzantines, the Seljuks and the Ottoman Empire. Sinop Castle, which could survive until today, has a length of 880 m in the North, 500 m in the east, 400 m in the south and 273 m in the west, and it defines the old borders of the city. It is observed that northern city walls of castle (Kumkapi Site) have been subjected to natural influences due to the its location and it is in danger of collapse. The purpose of scientific research on materials used in historical buildings; to obtain more information about visual, physical, mechanical and mineralogical properties of materials used in these structures. Using this information, suggestions on material selection to be used in the restoration of structures will be presented. In this study, stone and mortar samples were taken from the northern city walls of castle (Kumkapi Site) under the necessary laws and regulations. It was paid attention for the stone and mortar samples taken from the area at the sea level of the castle were intact. Samples of stone and mortar are masonry samples on the front surface, filler part and back surface of the castle. As physical analyzes on the samples; water absorption rates (bulk/ weight), real density, apparent density, porosity, and pressure resistance tests as mechanical analysis were applied. In accordance with the results obtained, the suitability of the material with the material values used in the literature was emphasized. In addition, it was aimed to suggest restoration proposals that compare the mortar samples taken from the castle walls with the mortar samples of some researchers in the literature.